Physics-of-failure lifetime prediction models for wire bond interconnects in power electronic modules - Yang, Li; Agyakwa, Pearl A.; Johnson, C. Mark (Institute of Electrical and Electronics Engineers, 2013)
This paper presents a review of the commonly adopted physics-of-failure-based life prediction models for wire bond interconnects in power electronic modules. In the discussed models, lifetime is generally accounted for by loading temperature extremes alone. The influence of the time spent at temperature on bond wear-out behavior and damage removal phenomena resulting from thermally activated processes is not addressed. The phenomenological considerations based on some unusual observations highlight the need for new approaches to wire bond life prediction models and thus motivate the proposal of a new time-domain damage-based crack propagation model.